PERDAGANGAN DALAM ISLAM: KAJIAN KUALITATIF TERHADAP AL-QUR’AN, HADIS, DAN INTERPRETASI ULAMA DI ERA MODERN - Sherly Mulyana (CV. KAMPUS AKADEMIK PUBLISING, 2024)
STrade in Islam is not only an economic activity, but also a means to achieve social welfare and blessings. The basic concepts in Islamic commerce, such as honesty, justice, and the prohibition of usury, are relevant guidelines in both traditional and modern contexts. Technological developments, such as e-commerce and cryptocurrencies, present new challenges and opportunities that require adjustment to sharia principles. Classical and contemporary scholars have provided profound interpretations related to the application of Islamic principles in modern commerce. Although modern commerce is more complex, Islamic teachings still provide a solid foundation to ensure that economic activities are not only oriented towards personal gain, but also oriented towards the welfare of the community.